Kesehatan Mental dan Pendidikan Agama Islam Mahasiswa di STIKES Griya Husada Sumbawa - Lina Eta Safitri; Ovi Soviya (Jurnal Anestesi, 2025)
Student mental health is an important aspect that needs to be considered in higher education, including at STIKES Griya Husada Sumbawa. A stressful and demanding academic environment can affect students' mental health. This research aims to identify factors that support mental health, with a focus on the role of Islamic religious education. Religious education not only teaches spiritual values, but also forms positive character and ethics. Using a qualitative approach, this research involved 30 students from the Public Health, Nursing and Midwifery study programs. The research results show that students who are active in religious activities have lower stress levels and better social support. Islamic religious education functions as a protective factor that increases students' mental resilience, helping them develop positive attitudes in facing challenges. These findings emphasize the importance of integrating religious education with mental health programs on campus to create an academic environment that supports student well-being.